The 11,800-year pollen-based vegetation (biome) reconstruction obtained from Razlomnoe Peat in the Lake Onega region (Eastern Fennoscandia) ... - Krikunova, Aleksandra I; Savelieva, Larisa A; Long, Tengwen; Leipe, Christian; Kobe, Franziska; Kostromina, Natalia A; Vasilyeva, Aleksandra V; Tarasov, Pavel E (PANGAEA, 2024)
The 885-cm-long sediment core RZ19 (62°27′53′′N, 34°26′4′′E) was retrieved in 2019 from Razlomnoe Peat (northern shore of Lake Onega), radiocarbon-dated and analysed for pollen and cryptogam spores. The age-depth model suggests continuous sedimentation since ca. 11,800 a BP. A total of 97 sediment samples (each representing a 2-cm layer) were selected for palynological analysis. Palynomorphs were extracted using standard laboratory techniques applied to lacustrine and peat sediments (Fægri and Iversen, 1989; Krikunova et al., 2022). One tablet with a known number of Lycopodium spores was added to each sample prior to chemical treatment in order to calculate pollen concentration (PC, Stockmarr, 1971) and pollen accumulation rates (PAR, Knight et al., 2022). Data contains results of biome scores published in Krikunova et al. (2024): https://doi.org/10.1016/j.quaint.2024.04.003 ...